Cognitive and emotional disorders in multiple sclerosis. Can a management strategy be envisioned? - Pelletier, J; Benoit, N; Montreuil, M; Habib, M (Pathologie biologie (Paris), 2000)
There is a lack of precise data concerning the natural history of cognitive disorders in multiple sclerosis (MS), but recent neuropsychological studies have demonstrated that the incidence of such disorders in MS appears to be frequent (40-65% of cases), and have shown in particular that recent memory, conceptual reasoning, attention, executive functions, visuospatial perception and information processing speed are negatively affected. In contrast, language functions, general intelligence and implicit memory appear to be relatively well preserved. Although the presence and the degree of cognitive disorders does not seem to be directly linked to disease duration or to the extent of physical disability, the relationship between cognitive decline and brain lesions detected by magnetic resonance imaging (MRI) is still a subject of discussion. The prevalence of emotional and affective disorders is difficult to estimate. Their frequency has only rarely been investigated, and the lack of data on the natural history of these disorders and those factors which they have in common (the psychosocial consequences of this chronic and disabling disease, cognitive impairment, and brain lesions) further complicate the determination of treatment strategy. The adoption of appropriate strategies could limit the negative impact of this disease on the social functioning of MS patients.